Community Empowerment through Training on Making Various Flavored Cavendish Banana Chips to Improve the Community Economy - Fauzi, Rif'an (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2025)
This study uses a qualitative method with a descriptive-analytical approach to examine community empowerment through training in making Cavendish banana chips with various flavors as an effort to improve the community's economy. This research was conducted in Karangsono Village, Wonorejo District, Pasuruan, on July 20 – August 25, 2024. Data was obtained through observation, interviews, and documentation with the main data sources of the village community, especially cadre women and youth groups. The analysis was carried out in a descriptive-qualitative manner using content analysis techniques to evaluate the effectiveness of the program. The results of the study show that this training has succeeded in improving people's skills in processing bananas into high-selling value products and encouraging awareness of innovation and marketing of local products. It is proven that empowerment based on local potential can improve the economic welfare of the community and encourage the sustainability of village MSMEs.